Universal Health Coverage: A Factor for Sustainable Development - Francis, Roselin; Vincent, Theresa Nithila (International Journal of Psychosocial Rehabilitation, 2020)
The first time World Health Organization pinned Universal Health Coverage as a focal point was in the year 2010 in their World Health Report. Since then UHC has been a heated topic of discussion among researchers, academicians, industry experts and the governments across the globe including India (Greer & Mendez, 2015). According to the World Health Statistics of 2017, there are seven factors that have been taken into account in order to monitor health for Sustainable Development Goals (SDGs). One of these seven factors is Universal Health Coverage (World Health Statistics, 2017)